Pendekatan Alami: Efektivitas Ekstrak Daun Sirsak, Serai, dan Daun Pepaya terhadap Larva Nyamuk - Efriza, Efriza; Ayu Asyifa, Frisca; Iswahyudi Yasril, Abdi (Ridwan Institute, 2024)
Dengue fever is caused by the dengue virus, which is transmitted by the Aedes aegypti mosquito. Dengue fever remains a significant health issue in tropical and subtropical countries. Various preventive measures, including vector control, are undertaken to reduce dengue fever infections. This study aims to assess the effectiveness of soursop leaf + lemongrass extract, soursop leaf + papaya leaf extract, and lemongrass + papaya leaf extract at a 50% concentration in controlling the vector of dengue fever using larvicides. In this research, extracts from the aforementioned plants were prepared and tested for their effectiveness against Aedes aegypti larvae. The larvae were exposed to different extract combinations, and their mortality rates were recorded over a specific period. The results were statistically analyzed to determine the significance of the findings. The analysis showed a significant difference in the average mortality of larvae using the soursop leaf + lemongrass extract combination and the soursop leaf + papaya leaf extract combination (p<0.05). These findings highlight the potential use of natural plant extracts in managing mosquito populations, particularly Aedes aegypti. In efforts to prevent and control dengue fever cases, the use of soursop leaf + lemongrass extract and lemongrass + papaya leaf extract as natural larvicides is recommended. It is crucial for community involvement, public health organizations, and policymakers to adopt natural pest control methods and consider integrating these natural solutions into public health strategies.